Automated high-dose rate brachytherapy treatment planning for a single-channel vaginal cylinder applicator. (5th May 2017) - Zhou, Yuhong; Klages, Peter; Tan, Jun; Chi, Yujie; Stojadinovic, Strahinja; Yang, Ming; Hrycushko, Brian; Medin, Paul; Pompos, Arnold; Jiang, Steve; Albuquerque, Kevin; Jia, Xun
Abstract: High dose rate (HDR) brachytherapy treatment planning is conventionally performed manually and/or with aids of preplanned templates. In general, the standard of care would be elevated by conducting an automated process to improve treatment planning efficiency, eliminate human error, and reduce plan quality variations. Thus, our group is developing AutoBrachy, an automated HDR brachytherapy planning suite of modules used to augment a clinical treatment planning system. This paper describes our proof-of-concept module for vaginal cylinder HDR planning that has been fully developed. After a patient CT scan is acquired, the cylinder applicator is automatically segmented using image-processing techniques. The target CTV is generated based on physician-specified treatment depth and length. Locations of the dose calculation point, apex point and vaginal surface point, as well as the central applicator channel coordinates, and the corresponding dwell positions are determined according to their geometric relationship with the applicator and written to a structure file. Dwell times are computed through iterative quadratic optimization techniques. The planning information is then transferred to the treatment planning system through a DICOM-RT interface. The entire process was tested for nine patients. The AutoBrachy cylindrical applicator module was able to generate treatment plans for these cases with clinical grade quality. Computation times varied between 1 and 3 min on an Intel Xeon CPU E3-1226 v3 processor. All geometric components in the automated treatment plans were generated accurately. The applicator channel tip positions agreed with the manually identified positions with submillimeter deviations and the channel orientations between the plans agreed within less than 1 degree. The automatically generated plans obtained clinically acceptable quality.